Cardiac involvement in the muscular dystrophies. Issue 5 (28th November 2017) - Silvestri, Nicholas J.; Ismail, Haisam; Zimetbaum, Peter; Raynor, Elizabeth M.
ABSTRACT: Cardiac disease is a common clinical manifestation present in a variety of neuromuscular disorders, most notably the muscular dystrophies. Heart disease may produce the presenting or predominant symptoms in these disorders but more often not does not result in clinical features at the time of initial presentation. Cardiac involvement in the muscular dystrophies results from pathologic changes in the myocardium and the cardiac conduction system, leading to cardiomyopathy and/or rhythm disturbances including supraventricular arrhythmias, life‐threatening ventricular arrhythmias, and sudden cardiac death. This Review covers the spectrum of cardiac dysfunction in these inherited muscle disorders and proposes practical recommendations for monitoring and management. Muscle Nerve 57 : 707–715, 2018